2018
DOI: 10.3892/mco.2018.1779
|View full text |Cite
|
Sign up to set email alerts
|

Histological complete response with nivolumab for renal cell carcinoma with multiple metastases: A case report

Abstract: The present case report describes a case of left renal clear cell carcinoma with brain, lung, para-aortic, and lymph node metastases (cT1bN1M1) in a 52-year-old Japanese male. The patient received sequential anticancer treatments with pazopanib, everolimus, and axitinib, but exhibited treatment-resistant tumor growth. Treatment with nivolumab resulted in a complete response in metastatic sites. However, the residual renal tumor, which was enhanced by contrast medium, required radical nephrectomy. Pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…As such, infiltration of CD8 + cells in tumor may potentially predict the effectiveness of pembrolizumab in this case. Similar histological findings had been observed in renal cell carcinoma wherein nivolumab promoted a pathological complete remission (10,11). On the other hand, biopsy and resected specimens had a similar density of CD8 + cells with a high Ki67 expression.…”
Section: Discussionsupporting
confidence: 76%
“…As such, infiltration of CD8 + cells in tumor may potentially predict the effectiveness of pembrolizumab in this case. Similar histological findings had been observed in renal cell carcinoma wherein nivolumab promoted a pathological complete remission (10,11). On the other hand, biopsy and resected specimens had a similar density of CD8 + cells with a high Ki67 expression.…”
Section: Discussionsupporting
confidence: 76%
“…The number of CD8-positive T cells in biopsy specimens may predict nivolumab treatment response in metastatic RCC. 9,10 Choueiri et al reported that increased PD-L1 expression in tumor cells and increased number of CD8-positive T cells in the tumor were associated with decreased survival in patients receiving first-line endothelial growth factor receptor-targeting agents (i.e. pazopanib or sunitinib).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional analysis identified the up-regulation of genes stimulated by interferon Îł with high levels of related chemokine in peripheral blood. A study case reported a histological complete response after nivolumab in metastatic ccRCC [41]. Only fibrotic changes and CD8+ lymphocytes were detected after treatment.…”
Section: Immune Componentmentioning
confidence: 99%